The Enlightened Path: Muḥammad ‘Abduh's Fusion of Reason and Revelation - Gilang Febiyanto, Aditiya; Najib Azka, Andhika (Mauriduna: Journal of Islamic Studies, 2024)
This research paper, titled "The Enlightened Path: Muḥammad ‘Abduh's Fusion of Reason and Revelation," explores the transformative influence of Muḥammad ‘Abduh’s rationalist theology on modern Islamic thought. Focusing on his seminal work "Risālat al-Tawḥīd" the study examines how Abduh’s integration of reason and revelation has provided a framework for a dynamic and progressive interpretation of Islamic teachings in particular contemporary theology. The research highlights Abduh’s belief in the compatibility of faith and reason, arguing that rational thought is essential to truly understand God’s unity (Tawḥīd) and Islamic ethics. This research demonstrates the continuing significance of Abduh's rationalist theology and offers a helpful framework for negotiating the challenges of modernity, identity, and religion. It asks for more investigation into the long-term effects of Abduh's theories, theological comparisons, and real-world implementations of his reforms in Muslim countries today. Muḥammad 'Abduh has shown by his enlightened path that revelation and reason can coexist peacefully, each enhancing the other and leading to a deeper and more applicable understanding of Islam in the contemporary world.